Welfare Professions in Transition - Kamp, Annette (Nordic Journal of Working Life Studies, 2016)
Welfare professions constitute one of the backbones in the development of the Nordic welfare states. Working in the public sector was for decades associated with high status; public sector employees were trusted employees. Through their work, they had important responsibilities for the welfare state and its citizens. To provide job security—through employment as officials—was a part of ensuring the stability of the state (Åkerstrøm, 2001), and we saw the establishment of what could be called a public ethos, a special morality aimed at serving the needs of the citizens and the state (Hoggett, 2005). The term welfare professions is widely used, referring to public sector employees in the field of, for example, health, education, care, and social work. So this term covers professionals who work directly in contact with patients, citizens, clients, students, etc. (Brante, 1990; Järvinen & Mik-Meyer, 2012). Along with the development and modernization of the welfare state, a number of new welfare professions, such as pedagogues, social works, physiotherapists, social care assistants, and auxiliary nurses have joined the existing ones like nurses, teachers, psychologists, and physicians. At the same time, however, the public sector has undergone dramatic changes as part of a neoliberal transformation of the welfare state. With the New Public Management (NPM) wave from 1980s and onwards efforts to restructure public institutions and introduce market-like relationships between them, to outsource and privatize public services and to transform citizens to customers in a market have prevailed (Busch, 2005; Christensen & Lægreid, 2007; Greve, 2008). Within this reform strategy, welfare professionals are perceived as part of the problem that NPM is created to solve, namely an uncontrollable and wildly growing bureaucracy (Clarke & Newman, 1997) (...)